Iena-Frankfurt-Iena: Hegel, Hölderlin e o nascimento do Idealismo alemão (Revista Eletrônica Estudos Hegelianos, 2021)
This article pretends to summarize the philosophical trajectories of two German thinkers of the end of the 18thcentury: Georg Friedrich Hegel and Friedrich Hölderlin. Having this goal in mind, we want to focus on their reciprocal influence and their contributions to the formation of the German Idealism. Special attention will be given to the period between 1795 and 1806, starting with Hölderlin’s move to Jena, passing through the period when both friends lived in the same city, Frankfurt am Main, and finishing with Hegel’s years in Jena. The idea behind this trajectory is to expose the development of their philosophical thoughts: the critical views on Fichte’s Wissenschaftslehre, the influence of the Vereiningungsphilosophieof authors such as Herder and Shaftesbury, and, finally, the first traces of Hegel’s system. We also pretend to emphasize Hölderlin’s significant – and often ignored - contribution to Hegel’s development as a thinker and the strength of his philosophical views.